Analisis Kesalahan Mahasiswa Pendidikan Matematika Dalam Menyelesaikan Soal Pertidaksamaan Pada Mata Kuliah Kalkulus I - Rahmawati, Ana (Universitas Islam Raden Intan Lampung, INDONESIA, 2017)
This research is qualitative descriptive research. This research has purpose to describe student error in resolving matter inequality of calculus I. The subject of this research is taken from student of mathematics education Unipdu semester II academic year 2016/2017. Data collection method used in this research is using test method and interview method. Before the researchers conducted the analysis, the researchers examined the validity of data using time triangulation to obtain valid data. Then from the data that has been validly analyzed new then drawn a conclusion. From result of research got result that 1) Subject A do 9 kind of errors, that is: error in determining condition of a root, mistake in doing process calculation, error determines value x on a number line, mistake determines set of settlement, error in determining sign interval at Line of numbers, errors in determining the completion region on the line of numbers, the error in determining the value of the zero maker on the split points, the error in determining the value of the zero-maker on the number line, the error of not continuing the completion process; 2) Subject B performs 8 types of errors, the type of error is the same as subject A, except error in determining the requirements of a root.